2018
DOI: 10.1002/hpja.197
|View full text |Cite
|
Sign up to set email alerts
|

Health Star Ratings: What's on the labels of Australian beverages?

Abstract: We found that there are low uptake and limited use of the HSR System on beverages. SO WHAT?: The HSR System on beverages could better achieve its objectives if the energy-only icon were removed from the graphic options, the algorithm were adjusted so that 100% juices cannot display a 5-star rating, and the System were made mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Uptake had been examined in five peer‐reviewed publications 64,67,71,83,84 and six government‐commissioned reports 23,31,85–88 covering both Australia and New Zealand. Results indicated uptake was increasing, with government issuing a communiqué in June 2018 that HSR had been displayed on 10,333 products in Australia and over 3,900 in New Zealand 89 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uptake had been examined in five peer‐reviewed publications 64,67,71,83,84 and six government‐commissioned reports 23,31,85–88 covering both Australia and New Zealand. Results indicated uptake was increasing, with government issuing a communiqué in June 2018 that HSR had been displayed on 10,333 products in Australia and over 3,900 in New Zealand 89 .…”
Section: Resultsmentioning
confidence: 99%
“…Official monitoring also suggested >90% accuracy of HSR values, with incorrect calculations more frequently under‐reporting, rather than over‐stating HSR, usually by 0.5 stars 23,31,87 . Independent research raised issues concerning inconsistent use of the ‘energy icon only’ variant of HSR, particularly on low‐scoring non‐dairy beverages 83,84 …”
Section: Resultsmentioning
confidence: 99%
“…4 fl oz) of juice to replace a serve of fruit "occasionally." Australia and New Zealand have adopted an interpretive front-of-pack labelling scheme (Health Star Ratings); however, use of the scheme by manufacturers is voluntary and as a result there is low uptake across SSBs [26]. Furthermore, the scheme awards many fruit juices the healthiest ranking along with water.…”
Section: Introductionmentioning
confidence: 99%
“…While recall of the HSR was reasonable in this sample, it cannot be expected to be very high because it is only on a limited number of products. 1 Overall confidence in using the HSR may improve if recommended changes to the HSR system from the current review are fast-tracked to address any design issues and anomalies, reported positively in the media, and that the system is made mandatory for all packaged foods. 8…”
Section: Recall Of and Confidence In Using The Health Star Rating Sysmentioning
confidence: 95%